Assessment of Treatment Effectiveness of Allergic Conjunctivitis in Children and its Impact on Quality of Life (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This article presents the results of a comprehensive study of the clinical and immunological features of allergic conjunctivitis in children and an assessment of the effectiveness of treatment, taking into account the impact of therapy on patients' quality of life. One hundred and fifty children aged 6 to 17 years, observed at the Bukhara branch of the Republican Scientific Specialized Center of Allergology and the Republican Specialized Center for Eye Microsurgery, were examined. The study included an assessment of clinical symptoms, immunoglobulin ( IgA , IgM , IgG , IgE ) and cytokine (IL-6, IL-10) levels, and a quality of life analysis using the Pediatric Quality of Life Inventory ( PedsQL ) scale. The results demonstrate that complex treatment with immunomodulatory elements provides a lasting therapeutic effect, reduces the frequency of relapses, and significantly improves the quality of life of children with allergic conjunctivitis.